Whole-body vibration as a method of recovery for soccer players - Marin, P. J.; Zarzuela, R.; Zarzosa, F.; Herrero, A. J.; Garatachea, N.; Rhea, M. R.; Garcia-Lopez, D. (European Journal of Sport Science, 2012)
The aim of this study was to determine whether superimposed whole-body vibration could improve the recovery-related effects of a traditional cool-down in high-level soccer players. Sixteen high-level junior soccer players performed a repeated-sprint ability test, after which they performed a traditional cool-down, with (experimental group) or without (control group) superimposed whole-body vibration. Functional recovery was measured through vertical jump height and maximal voluntary isometric force in leg-extension. The repeated-sprint ability test induced increases (from 161 to 215%; P<0.05) in muscle pain measured by visual analogue scale in the control group only. Vertical jump height was recovered earlier with than without whole-body vibration (24 h after the repeated-sprint ability test; P<0.05). The results of this study demonstrate that whole-body vibration in combination with a traditional cool-down can reduce perceived muscle pain and enhance recovery after a soccer-specific exercise.